Emergency uncross‐matched blood transfusions in a tertiary neonatal unit. (February 2017) - Finn, D; Dorrian, A; Sheehy, J; Dempsey, EM; Ryan, CA
Abstract: Aim: To determine the neonatal incidence, indications and outcomes following transfusions with emergency uncross‐matched O‐negative blood. Methods: A five‐year retrospective review in a single tertiary neonatal unit was conducted. The blood transfusion laboratory's database was analysed for all infants who had received an emergency released blood transfusion (ERBT) between January 2010 and December 2014. Results: We calculated a total ERBT rate of 0.91 per 1000 live births (39/42 657) and a rate of 0.43 per 1000 in infants >34 weeks' gestation (18/41 637). A rate of 0.14 per 1000 births (6/42 657) received an ERBT as part of newborn stabilisation despite almost half of our infant cohort having intrapartum haemorrhages (n = 18, 46%). One‐third (13/39) of all infants who were transfused died. Outcome varied depending on underlying aetiology, gestation and birthweight. The highest mortality was in preterm infants weighing <1000 g, of whom 70% died. Conclusion: This study establishes an ERBT rate of <1 per 1000 births, and 0.14 per 1000 infants received an ERBT as part of newborn delivery room stabilisation. ERBTs are associated with a high mortality rate. This study highlights the need for further research and guidelines that clarify the role of ERBTs in newborn stabilisations.